Creating a balance between breathing and viability: experiences of well-being when living with chronic obstructive pulmonary disease. Issue 1 (14th February 2014) - Stridsman, Caroline; Zingmark, Karin; Lindberg, Anne; Skär, Lisa
Abstract : Aim: To describe experiences of well-being among people with moderate to very severe chronic obstructive pulmonary disease (COPD). Background: Living with COPD is related to a complex life situation, and quality of life (QOL) is shown to decrease because of respiratory symptoms and fatigue. However, studies describing well-being in COPD as a subjective description of QOL are rare. Methods: Ten participants with moderate to very severe COPD from the Obstructive Lung Disease in Northern Sweden (OLIN) COPD study were interviewed about their experiences of well-being. A latent qualitative content analysis was used to analyse the data. Findings: To achieve well-being despite breathlessness, the participants had to adapt to their limitations and live towards the future. They created a balance between breathing and viability by adjusting to a lifelong limitation, handling variations in illness, relying on self-capacity and accessibility to a trustful care. The participants adjusted to lifelong limitations through acceptance and replacement of former activities. They handled variations in illness by taking advantage of the good days and using emotional adaptation strategies. The participants relied on their own self-capacity, feeling that smoking cessation, physical activity and breathing fresh air increased their well-being. They requested accessibility to a trustful care and highlighted the need for continuous care relationships and access to medications. These findings can enhance health-care professionals' understanding of the possibilities for increased well-being for people living with COPD.